(Dis)Integrating Visions: South and Imperial/Colonial Difference in Dickens and Conrad (Altre Modernità, 2017)
Albeit late with respect to the Iberians, the English contributed in a hegemonic way to the rise of Euro-Modernity, or that geocultural identity which emerged as the central site for the control of the world. Further to the idea of East, the idea of South has been central to British cultural imagination and has helped the rise of Englishness and of the European imperial master narrative. Therefore, the aim of this paper is to examine - through the tool of decolonial thinking – in which way the South/North division contributed to the emergence of European and British modern identity and, at the same time, to the inoculation of its disintegration virus. I will start with some reflections on world mapping and world imaging in European cultural history, emphasizing how histor(icit)y has made geography unreal and local Western iconography has created a global fictional world, in which we all dwell even today. I will then proceed with a brief survey on the concept of “coloniality of power”. Finally, I will try to tackle the idea of South as a literary topos in Charles Dickens’ Pictures from Italy (the beginning of Victorian age apogee) and Joseph Conrad’s Heart of Darkness (the end of it), examining to what extent they reflected the North/South dichotomy and partook of the (dis)integrating discursive formations of Meridionism and Australism.